2019
DOI: 10.3390/fi11060129
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Deployment of an End-To-End IoT Infrastructure for the Natural Environment

Abstract: Internet of Things (IoT) systems have seen recent growth in popularity for city and home environments. We report on the design, deployment, and use of the IoT infrastructure for environmental monitoring and management. Working closely with hydrologists, soil scientists, and animal behaviour scientists, we successfully deployed and utilised a system to deliver integrated information across these two fields in the first such example of real-time multidimensional environmental science. We describe the design of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…Due to their high customization capabilities, a popular WSN configuration, uses Arduino sensors [56] to generate environmental measurements and utilizes the ZigBee module for communication purposes, as described by Satyanarayana and Mazaruddin [57] and Papamichail et al [58], whilst extensively documented by Kooijman [59]. However, with the coming of IoT, more microcontrollers have come to light in order to support or even remotely control the Arduino processes, such as Raspberry Pis [60,61], which can be setup to act as sensors [62], gateways [63], databases [64], servers [65] or fog devices [66].…”
Section: Wsns In the Agricultural Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their high customization capabilities, a popular WSN configuration, uses Arduino sensors [56] to generate environmental measurements and utilizes the ZigBee module for communication purposes, as described by Satyanarayana and Mazaruddin [57] and Papamichail et al [58], whilst extensively documented by Kooijman [59]. However, with the coming of IoT, more microcontrollers have come to light in order to support or even remotely control the Arduino processes, such as Raspberry Pis [60,61], which can be setup to act as sensors [62], gateways [63], databases [64], servers [65] or fog devices [66].…”
Section: Wsns In the Agricultural Domainmentioning
confidence: 99%
“…The abundance of such devices has triggered new methods that provide increased land coverage, reliable transmissions, flexibility and scalability, even under harsh environmental conditions. For example, the authors of [63] reported the design and development of an end-to-end system in Northern Wales comprising Arduino sensors and incorporating Raspberry Pis, used as gateways for interconnection with a cloud server.…”
Section: Wsns Challenges and Opportunitiesmentioning
confidence: 99%
“…A multi-mobile agent travel planning algorithm (CL-MIP) is proposed in the literature [7]. It divides the problem of multi-mobile agent WSNs into four steps: (1) calculating the density center of the source node in the network; (2) taking the density center as the center of circle, with the predefined radius, the source nodes that are covered are grouped into one group; (3) computing the order in which each mobile agent accesses the source nodes in the group; (4) continuing to iterate until there is no unmarshalled node in the network, and sending multiple mobile agent packets in parallel. A system structure for the research of multi-mobile agent travel planning is provided by CL-MIP.…”
Section: Related Researchmentioning
confidence: 99%
“…The following problems are presented in single agent data. 1 Larger latency: when a single agent needs to access hundreds of nodes. 2 Load imbalance: the use of a single agent results in two kinds of energy consumption imbalance.…”
Section: Multiple Intelligent Agent Route Planning (Mip)mentioning
confidence: 99%
See 1 more Smart Citation